DIGITAL TECHNOLOGY The mixed reality medical ward round with the MS HoloLens 2: Innovation in reducing COVID-19 transmission and PPE usage. Issue 1 (2021) - Levy, Jeremy B; Kong, Edmund; Johnson, Nathan; Khetarpal, Ashni; Tomlinson, James; Martin, Guy FK; Tanna, Anisha
No abstract available